INJIL DAN ISLAM ABANGAN JAWA: SUATU PENDEKATAN KONTEKSTUAL: GOSPEL AND ISLAM ABANGAN IN JAVA: A CONTEXTUAL APPROACH - soerono tan (Jurnal Teologi Amreta (ISSN: 2599-3100))
"Whither Muslim evangelism in the 2000’s?" thus the questionthe care of Phil Parshall. According to Parshall, it's not like 1980when things become missionary in an Islamic country it becomes a trend andpride, the 2000s were marked by the slack mission to the Islamic world.It's really unfortunate even though Islam is the most religionfast growth in this world.Just as in a very pluralistic Christianity, so too is Islam. One of the big blocks (about 70%) that make up the Islamic world is what is called, "Abangan Islam," (English, "Folk Islam" or "Popular Islam"). This type of Islam issyncretistic, mainly characterized by an animistic worldview.In Indonesia, Javanese Abangan Islam is a very appropriate representationfrom this class of Islam. This paper will try firstlaying out the biblical basis for the practice of contextualization in brief,then followed by an understanding of the Javanese Islamic worldview and finally closed with an effort to find a "theological bridge" to reach the Javanese Islamic group effectively. === “Whither Muslim evangelism in the 2000’s?” demikian pertanyaan kepedulian dari Phil Parshall.  Menurut Parshall, tidak seperti tahun 1980an ketika hal menjadi misionaris di negara Islam menjadi suatu tren dan kebanggaan, tahun 2000-an diwarnai kendurnya misi ke dunia Islam.  Sungguh patut disayangkan padahal Islam merupakan agama yang paling cepat pertumbuhannya di dunia ini.  Sama seperti dalam kekristenan yang sangat majemuk, demikian juga Islam.  Salah satu blok besar (kira-kira 70 %) yang membentuk dunia Islam adalah apa yang disebut, “Islam Abangan,” (Inggris,  “Folk Islam” atau “Popular Islam”).  Islam golongan ini bersifat sinkretistik, utamanya diwarnai dengan pandangan dunia yang animistik.  Di Indonesia, Islam Abangan Jawa adalah representasi yang sangat tepat dari Islam golongan ini.  Makalah ini akan berusaha untuk pertama-tama meletakkan dasar alkitabiah bagi praktik kontekstualisasi secara singkat, kemudian disusul dengan pemahaman pandangan dunia Islam Jawa dan terakhir ditutup dengan usaha untuk menemukan “theological bridge” demi menjangkau kelompok Islam Jawa tersebut secara efektif.